2008
DOI: 10.1098/rspb.2008.0216
|View full text |Cite
|
Sign up to set email alerts
|

Global patterns in marine dispersal estimates: the influence of geography, taxonomic category and life history

Abstract: We examine estimates of dispersal in a broad range of marine species through an analysis of published values, and evaluate how well these values represent global patterns through a comparison with correlates of dispersal. Our analysis indicates a historical focus in dispersal studies on low-dispersal/low-latitude species, and we hypothesize that these studies are not generally applicable and representative of global patterns. Large-scale patterns in dispersal were examined using a database of correlates of dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
249
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 261 publications
(256 citation statements)
references
References 43 publications
6
249
1
Order By: Relevance
“…In a recent review, Bradbury et al (2008) asserted that dispersal studies have historically focused on "low-dispersal/low-latitude" species, and they suggested that these stud- Jones et al (1999) The data presented in this table are new. The data analysis and figures presented in this paper were based on these new data and the data presented in Shanks et al (2003a).…”
Section: Discussionmentioning
confidence: 99%
“…In a recent review, Bradbury et al (2008) asserted that dispersal studies have historically focused on "low-dispersal/low-latitude" species, and they suggested that these stud- Jones et al (1999) The data presented in this table are new. The data analysis and figures presented in this paper were based on these new data and the data presented in Shanks et al (2003a).…”
Section: Discussionmentioning
confidence: 99%
“…Even when the long larval dispersal distances of Pisaster and mussels (Wieters et al 2008) are taken into account, seston should disperse much more frequently, as it is constantly in the water column. Further, given the much longer pelagic larval duration of echinodermata relative to bivalves (Bradbury et al 2008), Pisaster should disperse more frequently over generational timescales between distant sites than mussels. Paine (1966) identified other analogous food webs where the consumer dispersal rate is expected to be less frequent than that of the predator or the resource; however, this dispersal structure is expected generally where the consumer is attached to a substrate.…”
Section: What Movement Mechanisms Can Lead Tomentioning
confidence: 99%
“…However, the efficacy of MPAs as well as the persistence and resilience of marine populations in the face of disturbances in general are fundamentally linked to the scale of dispersal and the degree of connectivity among populations (Eckert 2003;Botsford et al 2009). In addition, dispersal and connectivity drive population genetic differentiation and thus play key roles in the evolution of local adaptation (Bradbury et al 2008;Walter et al 2009). …”
Section: Introductionmentioning
confidence: 99%